SISTEM PENDUKUNG KEPUTUSAN OPTIMASI CAMPURAN BETON PRODUK K-300 PT SARANG LAKSANA MANDIRI - putra, hengky ayanto; Hazimah, Hazimah (LPPM Universitas Putera Batam, 2021)
ABSTRACT Sarang Laksana Mandiri is a manufacturing company in the readymix concrete manufacturing company located in Punggur-Batam, has the brand name Batam Beton, received complaints from consumers that the K-300 concrete product was not included in the quality criteria for the compressive strength of concrete so that when it was tested it reached 100%, meanwhile quality of concrete k-300 is concrete that can withstand loads weighing 300 kg / cm2 after 28 days of dry concrete. This study aims to determine the K-300 concrete design, by conducting experiments and then determining the K-300 product from civil engineering experts and concrete experience experts using the AHP and SAW methods with the criteria of dry time of concrete, compressive strength of concrete, concrete slump and material cost. aims to determine the best concrete design. The AHP method resulted in Kimson being globally superior from all criteria with a value of 0.40, Herry Huang, the second score was 0.32, the third Dwi scored 0.15, Eman scored 0.13. The SAW Kimson method is globally superior to all criteria with a value of 0.74, Herry Huang, the second score is 0.71, the third is Dwi with 0.68, Eman with 0.58.